2018
DOI: 10.1519/jsc.0000000000002412
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric Characteristics, Physical Fitness, and Throwing Velocity in Elite women's Handball Teams

Abstract: Saavedra, JM, Kristjánsdóttir, H, Einarsson, IÞ, Guðmundsdóttir, ML, Þorgeirsson, S, and Stefansson, A. Anthropometric characteristics, physical fitness, and throwing velocity in elite women's handball teams. J Strength Cond Res 32(8): 2294-2301, 2018-The aims of this study were (a) to analyze anthropometric, physical fitness, and throwing speed in women elite handball players of different ages and (b) to develop a multivariate model explaining handball performance from a multidimensional perspective. Eighty w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
1
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(73 citation statements)
references
References 25 publications
3
49
1
5
Order By: Relevance
“…There are also few reports on ball velocities in handball throws in adolescent players. Even though one study has reported an average throwing velocity as high as 108 km/h in adolescent male players, most studies have reported that adolescent male players' throws involve a ball speed between 72-86 km/h (15)(16)(17)(18) and female players between 65-83 km/h (19,20).…”
Section: Shoulder-specific Demandsmentioning
confidence: 99%
“…There are also few reports on ball velocities in handball throws in adolescent players. Even though one study has reported an average throwing velocity as high as 108 km/h in adolescent male players, most studies have reported that adolescent male players' throws involve a ball speed between 72-86 km/h (15)(16)(17)(18) and female players between 65-83 km/h (19,20).…”
Section: Shoulder-specific Demandsmentioning
confidence: 99%
“…Of the 41 studies included in the review, only one study was interventional in design [54], with the remaining observational in nature. Research in handball [54][55][56][57][58][59][60][61][62][63][64][65][66][67][68] was the most frequently included teambased, ball sport followed by volleyball [69][70][71][72][73][74][75][76][77][78][79][80]. Other sports investigated included soccer [81][82][83][84][85][86], basketball [87][88][89][90], netball [91,92], lacrosse [93], and softball [94].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Body composition was measured in 27 (66%) of the included studies [56, 58, 60, 61, 63-67, 69, 72, 73, 75-82, 85-87, 89-92]. Nine (22%) included studies examined cardiorespiratory fitness attributes [58,61,65,68,79,81,85,88,92]. Four (10%) studies examined coordination abilities [55,56,61,71].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations